Lower serum testosterone concentrations are associated with a higher incidence of dementia in men: The UK Biobank prospective cohort study. Issue 10 (3rd January 2022) - Marriott, Ross J.; Murray, Kevin; Flicker, Leon; Hankey, Graeme J.; Matsumoto, Alvin M.; Dwivedi, Girish; Antonio, Leen; Almeida, Osvaldo P.; Bhasin, Shalender; Dobs, Adrian S.; Handelsman, David J.; Haring, Robin; et al.
Abstract: Introduction: The association of testosterone concentrations with dementia risk remains uncertain. We examined associations of serum testosterone and sex hormone–binding globulin (SHBG) with incidence of dementia and Alzheimer's disease. Methods: Serum total testosterone and SHBG were measured by immunoassay. The incidence of dementia and Alzheimer's disease (AD) was recorded. Cox proportional hazards regression was adjusted for age and other variables. Results: In 159, 411 community‐dwelling men (median age 61, followed for 7 years), 826 developed dementia, including 288 from AD. Lower total testosterone was associated with a higher incidence of dementia (overall trend: P = .001, lowest vs highest quintile: hazard ratio [HR] = 1.43, 95% confidence interval [CI] = 1.13‐1.81), and AD ( P = .017, HR = 1.80, CI = 1.21‐2.66). Lower SHBG was associated with a lower incidence of dementia ( P < .001, HR = 0.66, CI = 0.51‐0.85) and AD ( P = .012, HR = 0.53, CI = 0.34‐0.84). Discussion: Lower total testosterone and higher SHBG are independently associated with incident dementia and AD in older men. Additional research is needed to determine causality.